Scaling Up Inclusive Approaches for Marginalised and Vulnerable People - Carter, Becky; Joshi, Anu; Remme, Michelle (2018)
This rapid review summarises the evidence on how to scale up inclusive approaches to complex social change. It looks at how to design scalab le inclusive change interventions, as well as how to plan and manage t he scale-up process. Focusing on interventions with the aim of reachin g the most marginalised and transform social norms, it covers programm es aiming to deliver inclusive outcomes for women and girls (with a pa rticular focus on preventing violence against women and girls) and per sons with disabilities. To date, many interventions seeking to change harmful gender and disability norms have been implemented as small-sca le projects. There are limited experiences of scale-up and fewer evalu ations of these experiences. However, there are some documented case s tudies as well as emerging analysis that draw out lessons learned. Fro m this evidence base, this rapid desk review identifies eight critical issues commonly highlighted as important considerations when scaling up inclusive change interventions: 1. Opportunities for systemic appro ach, including integrating political and community-level scale-up, and coordinating across multiple sectors and stakeholders 2. Political su pport for scale-up 3. Strategic choices: balancing reach, speed, cost, quality, equity, and sustainability 4. Catalysing change: tipping poi nts, diffusion effects, and local champions 5. Locally grounded, parti cipatory, and adaptive approaches 6. Long-term approaches with funding models to match 7. Cost-effective and financially feasible scale-up s trategies 8. Measuring impact and sustainability.